2010
DOI: 10.1016/j.trstmh.2010.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulated citronella oil for mosquito repellent finishing of cotton textiles

Abstract: Microcapsules containing citronella essential oil were prepared by complex coacervation and applied to cotton textiles in order to study the repellent efficacy of the obtained fabrics. Citronella released from treated textiles was indirectly monitored by the extractable content of its main components. Repellent activity was assessed by exposure of a human hand and arm covered with the treated textiles to Aedes aegypti mosquitoes. Fabrics treated with microencapsulated citronella presented a higher and longer l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(97 citation statements)
references
References 16 publications
1
74
0
4
Order By: Relevance
“…The plant essential oils were microencapsulated to prevent the easily evaporation process before the impart to fabric by pad dry cure method or addition to rinse cycle. Study by Specos stated that textile treated with microencapsulated citronella performed the higher and and longer lasting protection against mosquitoes compared to sprayed fabric with ethanol solution of essential oil (Specos et al 2010).…”
Section: Methods Of Imparting Repellent On Textile Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant essential oils were microencapsulated to prevent the easily evaporation process before the impart to fabric by pad dry cure method or addition to rinse cycle. Study by Specos stated that textile treated with microencapsulated citronella performed the higher and and longer lasting protection against mosquitoes compared to sprayed fabric with ethanol solution of essential oil (Specos et al 2010).…”
Section: Methods Of Imparting Repellent On Textile Materialsmentioning
confidence: 99%
“…Vigneshkumar and Specos et al reported the use of scoured and bleached cotton knitted fabric in a study determining the "Repellence effect of microencapsulated citrinellea oil on tretated textile fabrics against A. aegypti mosquitoes" and "Microencapsulated citronella oil for mosquito repellent finishing of cotton textiles" (Specos et al 2010;Vigneshkumar and Vijaykumar Vediappan 2012). Other study by Maheshwari et al (Maheshwari and Ramya 2014) utilized the same textile materials of cotton fabric which made from rib knitted and experiencing the scouring, bleaching and dyeing process in a study to determine eco friendly mosquito repellent fabric finished with natural plant.…”
Section: Textile Materials Used In Mosquito Repellency Studiesmentioning
confidence: 99%
“…Final product destination/effect References Peppermint Sedative, stimulatory, antiviral, and antibacterial properties [24] Citronella Mosquito repellent [25] Thyme Ocimum sanctum L.…”
Section: Essential Oilmentioning
confidence: 99%
“…The methods of simple coacervation and complex coacervation are widely used in traditional microencapsulation processes 34,35 ; in addition, simple coacervation is mainly used for encapsulating watersoluble drugs and complex coacervation is appropriate for water-soluble drugs. Besides the above-mentioned methods, there are some other preparation methods such as spray drying 36 , also mainly used for large-scale production.…”
Section: Microcapsulementioning
confidence: 99%